Alberto Cavallone tra divulgazione, mercificazione e provocazione (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
The work of Alberto Cavallone has never been properly studied by scholars. His low budget flicks had occasionally a little commercial success from 1968 (“Le salamandre”) to 1978 (“Blue Movie”). They deal with controversial topics – from homosexuality (both male and female) to decolonization – and show high ambitions and the explicit influence of Pasolini, Makavejev, Bataille and Fanon. Although overlooked by critics of their times for the cheap production values and the ambiguous exploitation of violent and sexual images, these movies show how certain themes could reach genre cinema, where a director like Cavallone could quote and remix highbrow culture with a baffling freedom.